The Impact of a Rehabilitation Program on Meniscal Tear Injury in Athletes - Mohammed, Duaa Athab; Jabbar, Ali Awad (South Eastern European Journal of Public Health, 2024)
The significance of the research lies in the preparation of a rehabilitation program for meniscus tear injuries in affected athletes, which aims to rehabilitate athletes from injuries that hinder their performance in their specialized sports. The problem of the research is that most athletes do not properly treat meniscus tear injuries and there is a lack of studies addressing this type of injury, which leads to functional impairment in the knee joint performance, preventing the player from practicing their specialized sport. The researchers used the experimental method for its suitability to the nature of solving research problems. The research sample included ten athletes with meniscus tears, selected intentionally. The aim of the research is to identify the effect of a rehabilitation program on meniscus tear injuries in affected athletes. The most significant conclusions were a clear improvement in the research group variables when using the rehabilitation program. The main recommendations were to generalize the used rehabilitation program to rehabilitation and physiotherapy centers in hospitals to apply it to affected individuals.